Crystal Chemistry Analysis of Ternary Phases in Systems Me-P-S(Se), where Ме – Ag, Cu, Zn, Cd, In, Tl, Sn, Pb - Voroshilov, Yu.V.; Milyan, Zh.I.; Мilyan P.М.; Potoriy, M.V. (Physics and Chemistry of Solid State, 2016)
Crystal structures ofternary thio(seleno)hypodiphosphates of metals of groups I-IV of the periodic system were analyzed. Chemical bonds in investigated phases were descripted on the base of interatomic distances in binary and ternary compounds.